MANAJEMEN PEMBELAJARAN DARING MASA PANDEMI COVID 19 DI SMA NEGERI 3 PONTIANAK - Usman Radiana; Rizky I'malia Sari; Ridha Sabda Utami; Hermawan Hermawan (Jurnal Education and Development, 2022)
To answer the problem of learning during the current COVID19 pandemic, various efforts have been made to adjust learning so that educational activities can continue. That is by using online learning. The facts in the field are many problems that arise in online learning. This study aims to describe the management of bold learning during the COVID-19 pandemic through management principles; 1) organizing; 2) financing; and 3) supervision. This study uses an approach with a case study type to analyze and describe how online learning management is during the COVID 19 pandemic at SMA Negeri 3 Pontianak. The results of this study indicate that the implementation of online learning is going well in accordance with the changes in the applicable curriculum. The allocation of costs is carried out effectively and efficiently in accordance with online learning needs and school needs such as learning facilities, health protocols, other facilities and infrastructure. Supervision of safe online learning is carried out by making a learning journal through the google form. The journal records students who experience obstacles in online learning, so that obstacles during online learning can be overcome.